Analisis Perancangan Stasiun Kerja dalam Memproduksi Produk Inalcafa Jacket dengan Lima Metode Line Balancing - Harun Indra Kusuma; Hadi Purnomo (G-Tech: Jurnal Teknologi Terapan, 2024)
The efficiency of a work system can be influenced by several factors, namely the operator and machine capacity in the production process. The line balancing method is the right method to increase the efficiency of a work system. From the various work stations, the researchers balanced the processing time of the work stations so that each line of work stations could complete quickly, thereby reducing waiting time. In this research, the researcher started the activity by collecting data from each work station in the process of making the Harrington Jacket which was produced by CV. 913 productions. From the results of the data obtained. Researchers processed data using Bill of Materials (BOM), Process Plan Sheet (LRP), Precedence Diagram, Assembly Chart, and Operation Process Chart (OPC). In order for the production process to be very efficient, methods are needed. The methods used are the Ranked Positional Weight (RPW) method, the Mirror RPW method, the Largest Candidate Rule (LCR) method, the J.Wagon method and the Region Approach method.